Why People Play at Work: A Theoretical Examination of Leisure-at-Work. (2nd November 2018) - Duerden, Mat D.; Courtright, Stephen H.; Widmer, Mark A.
ABSTRACT: Postmodern perspectives on work and leisure acknowledge the interwoven nature of these domains, an example being the increasing number of organizations intentionally incorporating leisure into the employee experience. Existing research, however, provides no specific theoretical guidance regarding the potential impacts of strategically integrating recreation activities into the work domain. Thus, based on positive organizational scholarship and leisure science theories, we build an individual level model describing the phenomenon of leisure-at-work (LAW). We propose LAW activities have the ability to produce feelings of personal expressiveness at work as moderated by employees' perceptions of the activities. Personal expressiveness then mediates LAW activities' ability to promote the development of organizational commitment, work engagement, and resilience among employees.